Weak and strong states in Asia-Pacific societies (St. Leonards, N.S.W. : Allen & Unwin, 1998)
Weak States, strong States. Why do so many states stay intact? In weakness and strength-State, societies and order in Papua new guinea...
Keywords: Politics; Asia; Southeastern; Melanesia; Asia, Southeastern -- Politics and government -- 1945-; Asia, Southeastern -- Social conditions -- 20th century; Melanesia -- Politics and government -- 20th century; Melanesia -- Social conditions -- 20th century